On the formation and chemical composition of super Earths - Alessi, Matthew; Pudritz, Ralph E.; Cridland, Alex J. (Monthly notices of the Royal Astronomical Society, 2017)
Super Earths are the largest population of exoplanets and are seen to exhibit a rich diversity of compositions as inferred through their mean densities. Here we present a model that combines equilibrium chemistry in evolving discs with core accretion that tracks materials accreted on to planets during their formation. In doing so, we aim to explain why super Earths form so frequently and how they acquire such a diverse range of compositions. A key feature of our model is disc inhomogeneities, or planet traps, that act as barriers to rapid type-I migration. The traps we include are the dead zone, which can be caused by either cosmic ray or X-ray ionization, the ice line, and the heat transition. We find that in discs with sufficiently long lifetimes (≳4 Myr), all traps produce Jovian planets. In these discs, planet formation in the heat transition and X-ray dead zone produces hot Jupiters, while the ice line and cosmic ray dead zones produce Jupiters at roughly 1 au. Super Earth formation takes place within short-lived discs (≲2 Myr), whereby the discs are photoevaporated while planets are in a slow phase of gas accretion. We find that super Earth compositions range from dry and rocky (<6 per cent ice by mass) to those with substantial water contents (>30 per cent ice by mass). The traps play a crucial role in our results, as they dictate where in the disc particular planets can accrete from, and what compositions they are able to acquire.